Neuro-ophthalmologic and blood biomarker responses in ADHD following subconcussive head impacts: a case–control trial - Nowak, Madeleine K.; Kronenberger, William G.; Rettke, Devin; Ogbeide, Osamudiamen; Klemsz, Lillian M.; Quinn, Patrick D.; Mickleborough, Timothy D.; Newman, Sharlene D.; Kawata, Keisuke (Frontiers in Psychiatry, 2023)
This clinical trial aimed to determine the influence of attention-deficit/hyperactivity disorder (ADHD) on neuro-ophthalmologic function and brain-derived blood biomarkers following acute subconcussive head impacts. The present trial consisted of age- and sex-matched samples with a ratio of 1:1 between two groups with a total sample size of 60 adults (age  SD; 20.0 1 .8 years). Soccer players diagnosed with and medicated daily for ADHD were assigned into an ADHD group (n=30). Soccer players without ADHD were assigned into a non-ADHD group (n=30). Participants performed 10 soccer headers with a soccer ball projected at a velocity of 25mph. King-Devick test (KDT), near point of convergence (NPC), and serum levels of NF-L, tau, GFAP, and UCH-L1 were assessed at baseline (pre-heading) and at 2 hours and 24 hours post-heading. There were no statistically significant group-by-time interactions in outcome measures. However, at baseline, the ADHD group exhibited lower neuro-ophthalmologic functions compared to the non-ADHD group (NPC: p=0.019; KDT: p=0.018), and persisted at 2 hours-post (NPC: p=0.007; KDT: p=0.014) and 24 hours-post heading (NPC: p=0.001). NPC significantly worsened over time in both groups compared to baseline [ADHD: 2 hours-post, 1.23cm, 95%CI:(0.77, 1.69), p<0.001; 24 hours-post, 1.68cm, 95%CI:(1.22, 2.13), p<0.001; Non-ADHD: 2 hours-post, 0.96cm, 95%CI:(0.50, 1.42), p<0.001; 24 hours-post, 1.09cm, 95%CI:(0.63, 1.55), p<0.001)]. Conversely, improvements in KDT time compared to baseline occurred at 2 hours-post in the non-ADHD group [-1.32s, 95%CI:(-2.55, -0.09), p=0.04] and at 24 hours-post in both groups [ADHD: -4.66s, 95%CI:(-5.89, -3.43), p<0.001; Non-ADHD: -3.46s, 95%CI:(-4.69, -2.23), p<0.001)]. There were no group-by-time interactions for GFAP as both groups exhibited increased levels at 2 hours-post [ADHD: 7.75pg/mL, 95%CI:(1.41, 14.10), p=0.019; Non-ADHD: 7.91pg/mL, 95%CI:(1.71, 14.14), p=0.015)] that returned to baseline at 24 hours-post. NF-L levels increased at 2 hours-post heading in the ADHD group [0.45pg/ml, 95%CI:(0.05, 0.86), p=0.032], but no significant NF-L changes were observed in the non-ADHD group over time. Ten soccer headers elevated GFAP levels and NPC impairment in both groups. However, persisting group difference in NPC, blunted KDT performance, and increased NF-L levels in the ADHD group suggest that ADHD may reduce neuro-ophthalmologic function and heighten axonal response to soccer headers.